Perancangan Buen Art Center di Penajam Paser Utara dengan Pendekatan Ikonik Pada Bentuk Bangunan - Nurzakiyah, Nurzakiyah; Ramadhani, Suci; Ratniarsih, Ika (Institut Teknologi Adhi Tama Surabaya, 2024)
The Penajam area is a district located in Penajam Paser Utara, East Kalimantan with 110,240 inhabitants and a total area of 3,333.06 km² in 2002. As long as North Penajam Paser was established, there was not a single Art Center building, and many festivals were often held in Penajam such as the Nondoi Festival, Belian traditional festival, Serambi Nusantara. So this design aims to create an Arts Center that will accommodate artistic activities in North Penajam Paser. The Buen Art Center was planned using an architectural approach that designs a building using data and social habits of a place, and something that is associated with an